Scaling climate-smart innovations in Ethiopia - Ewell, Hanna Louise Deborah; Carbonell Barlis, Angelica; Ambaw, Gebermedihin; Makonnen, Brook; Solomon, Dawit (2025)
Since 2021, Ethiopia has moved from piloting to systemic scaling of bundled CSA and CIS. AICCRA Ethiopia has reached 770,581 farmers, livestock keepers, and extension agents. 373,606 farmers received tailored digital advisories, over 95,000 livestock keepers accessed SmaRT packs, and 50,000 farmers benefited from forage innovations. Site-specific fertilizer recommendation increased yield by 16% and 25% compared to national and local blanket fertilizer rates, respectively, resulting in profit gains of USD 580 and USD 412 per hectare per season over local and national recommendations, respectively.